(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Today, the problem of developing artistic thinking in children of primary school age is of great importance in the educational process. The modern education system is aimed at developing the intellectual and creative abilities of children. Therefore, the process of teaching music is one of the effective tools for enriching the artistic world of students and improving their skills of imaginative thinking. Music education occupies a special place in the development of aesthetic taste, emotional intelligence and artistic thinking of children. In music lessons, students develop their thinking abilities through the influence of sound, rhythm, harmony and images and learn a deeper understanding of art. In modern pedagogy, the issue of revealing the creative potential of children, taking into account their individual characteristics, is acute. In this context, music lessons offer many opportunities. Through music, children have the opportunity to freely express their emotions, create images through musical pieces, develop their imagination and improve their creative thinking skills. The use of various teaching methods, innovative methods and technologies in the process of teaching music increases children’s interest. Interactive methods, game elements, musical staging and multimedia technologies improve children’s perception of music, deepen their imagination and aesthetic worldview. The relevance of this article is related to the need to strengthen the role of music lessons in the education system and the development of artistic thinking of primary school students. By developing effective methods of teaching music lessons and applying them in practice, the education system makes a great contribution to the development of students’ creative abilities and the expansion of their aesthetic worldview.